The Potential of Jenderal Soedirman's Short Film as Learning Media in National Events of the Colonial Period’s Material for Fifth Graders: A Semiotics Analysis - Supriatna, Encep; Savira, Ratu Tiara (Journal of Education Technology, 2021)
The stories of Jenderal Soedirman, one of the national instrumental figures in seizing Indonesia's independence from the invaders, have been visualized in many films. Films containing events about the struggle for independence need to be studied, understood and remembered so that the values of nationalism are embedded. This film has the potential to be used as a learning media in packaging stories into interesting and meaningful learning for elementary school students. This leads researchers to analyze Jenderal Soedirman’s short film as learning media on the IPS national events of the time colonization of 5th graders of elementary school. This study  used a qualitative approach in observing an individual behavior and to describe the data of research’s findings in detail and moderation. The research method used was Roland Barthes’s semiotic analysis that focused on signs and symbols as markers interpreted by denotation, connotation and myth on the film. The data collecting techniques used were observation, student's journal, questionnaires and documentation. Based on research and discussion of semiotic analysis of Jenderal Soedirman’s short film as learning media on three meanings, it is evident that researchers can better understand the hidden meaning contained in the film. The researchers deeply identify the figure of Jenderal Soedirman, the myth believed by the Indonesian freedom people during his  struggle and this film potential to be used as a learning media because it increases students’ learning motivation by a score of  3,00 earned in a reasonably good category.